2019
DOI: 10.31223/osf.io/7n6ub
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Urban Near-surface Seismic Monitoring using Distributed Acoustic Sensing

Abstract: Urban subsurface monitoring requires high temporal-spatial resolution, low maintenance cost, and minimal intrusion to nearby life. Distributed acoustic sensing (DAS), in contrast to conventional station-based sensing technology, has the potential to provide a passive seismic solution to urban monitoring requirements. Based on data recorded by the Stanford Fiber Optic Seismic Observatory, we demonstrate that near-surface velocity changes induced by the excavation of a basement construction can be monitored usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Therefore, this type of experiment can be rapidly deployed in a few hours and continue to record for years without major operations costs. In urban areas, DAS measurements have already been used for near surface geological imaging (Dou et al, 2017; Fang et al, 2020; Martin, 2018; Spica et al, 2020) and earthquake recording (Lindsey et al, 2017; Martins et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this type of experiment can be rapidly deployed in a few hours and continue to record for years without major operations costs. In urban areas, DAS measurements have already been used for near surface geological imaging (Dou et al, 2017; Fang et al, 2020; Martin, 2018; Spica et al, 2020) and earthquake recording (Lindsey et al, 2017; Martins et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In 2019 there are more than hundreds repeatable blast events cataloged from these sites, which could allow yearly near-surface monitoring of geotechnical engineering activities (Fang et al, 2020) and/or hydrological systems owing to a significant ground water level variation. One strong event, shown in Figure 14, was recorded on May 14 2019 from the site 4 (Pleasant Gap, PA).…”
Section: Mining Blastmentioning
confidence: 99%
“…This series of experiments have shown that signal quality is often good enough for earthquake detection and imaging even though loose cables in underground conduits only couple to the surrounding soils through friction and gravity (Lindsey et al, 2017;Jousset et al, 2018;Martin et al, 2019;Yu et al, 2019;Ajo-Franklin et al, 2019). At the Stanford Fiber Optic Seismic Observatory, Rayleigh wave dispersion showed significant spatial variability at scales relevant to earthquake ground motion prediction (Martin, 2018;Spica et al, 2020), and time-lapse changes through a building excavation (Fang et al, 2020). However, investigation of near-surface time-lapse changes due to seasonal precipitation variation yielded no significant velocity variation when investigated with time-lapse ambient noise interferometry (Martin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…By connecting a DAS interrogator at one end of a (potentially) tens-of-kilometres-long optical fibre, time-series measurements of ground deformation can be made at metre-spaced intervals along the cable. This emerging technology has massively extended our range of capabilities for seismic monitoring, enabling the deployment of dense seismic arrays in areas that were previously inaccessible, such as urban [2], [3] or submarine [4], [5] locations. Fibreoptic cables can be deployed on rugged terrain on land or underwater, are temperature-robust, and they are sensed ex-situ (i.e.…”
Section: Introductionmentioning
confidence: 99%